GetHealthyHarlem.org: Developing a Web Platform for Health Promotion and Wellness Driven by and for the Harlem Community - Khan, Sharib A. (American Medical Informatics Association, 2009)
GetHealthyHarlem.org is a community website developed on an open-source platform to facilitate collaborative development of health content through participatory action research (PAR) principles. The website was developed to enable the Harlem community to create a shared health and wellness knowledgebase, to enable discourse about local and culturally relevant health information, and to foster social connections between community members and health promotion organizations. The site is gaining active use with more than 9,500 unique site visits in the six months since going live in November, 2008. In ongoing research studies, we are using the website to explore how the PAR model can be applied to the development of a community health website.